Compact vertical emitting ring interband cascade lasers for isotope-resolved CO2 sensing - Georg Marschick; Stefania Isceri; Rolf Szedlak; Harald Moser; Johannes P. Waclawek; Elena Arigliani; Robert Weih; Werner Schrenk; Gottfried Strasser; Borislav Hinkov; Aaron Maxwell Andrews; Bernhard Lendl; et al. (APL Photonics, 2024)
We present a compact vertically emitting ring interband cascade laser (ICL) with low power consumption and the possibility for seamless integration into various CO2 sensing applications. Our devices exhibit desirable performance characteristics in battery-driven handheld devices, including room temperature (20 °C) threshold currents as low as 15 mA, small footprints, and stable single-mode emission, suitable for rapid isotope-resolved CO2 detection. Through epi-down bonding with sub-micron accuracy, we achieved robust integration of substrate-emitting ring ICLs, ensuring reliability and scalability that would be required for mass production. We present comprehensive experimental results validating the efficacy of our approach, including spectral analysis and CO2 sensing capabilities with limits of detection of 24 and 13 ppmv utilizing the 12CO2 P(60) and 13CO2 R(10) transitions in the ν3 fundamental band, respectively. The demonstrated devices hold great promise for a wide range of industrial applications, including environmental monitoring, process control, and atmospheric research, where compact low-power sensors are essential.